Effect of specific mineral supplementation on the blood profile of dairy cattle of Himachal Pradesh - VERMA, M S; KUMAR, R; SHARMA, K B (The Indian Journal of Animal Reproduction, 2023)
After initial assessment of mineral status of the animals, the selected animals were supplemented withspecifically formulated mineral mixture for 30 days. Resu(ts indicated si~ni_ficant in_crease in averageconcentrations of Ca p Na and Cl whereas Mg and K levels increased non-significantly in the blood of theanimals after specifid rriineral supplementation. The overall mean plasma Cu and Zn concentrations increasedsignificantly from 0:59 ± 0.03 to 0.70 ± 0.04 μg/!'11 and from 0.81 ± 0.04 μg/ml to_0.90 ± 0.0~ μg/ml respec_tivefiafter mineral supplementation. Numerically the number of anoestrous animals declined after mineralsupplementation but it was non-significant.
Keywords: Mineral supplementation; Cattle; Blood plasma; Anoestrous